Prospects of waterway development as a catalyst to improve regional and community socio-economy level - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Abu Samah, Asnarulkhadi; Abu Samah, Bahaman (Science Publications, 2010)
Problem statement: Malaysia has achieved a number of successes in its transportation development. The success of Kuala Lumpur International Airport and Northern and Southern Highway project for example have given the community a lot of benefits in term of social and economic development, but what if an inland waterway system can be developed in Malaysia especially along the Pahang River and Muar River. Can this proposed waterway bring significant impact to local people in term of their social and economic development? This has become the main objective of this study which is to investigate whether the future Pahang Muar Waterway could have significant socio-economic impact on the local community or not. Approach: This is a qualitative study. Observations, structured and unstructured in-depth interview and literature analysis were used to gain the data needed and the research team had traversed along these rivers (Muar to Bahau and ended in Pekan). For the in-depth interviews, a total of seventeen informants among the public and government officers were selected. Data from the in-depth interviews were transcribed verbatim and subsequently analyzed by identifying similarities and consistent themes. A constant comparative method was employed in order to uncover patterns in the data. The data in this study is presented descriptively. Results: From the observation, interviews and literature analysis done, it can be concluded that the Pahang Muar Waterways is believed to develop economic activities, recreational activities, tourism industry, enhance the socio-economic life of local community and provide sustainable mobility. onclusion/Recommendations: From the results gained, it can be concluded that a majority of the community interviewed believed that Pahang Muar waterways offer a vast opportunity for social and economic development for the local community. It can be noted that specific planning on constructing the inland waterways should be started by the local authorities. It is recommended that specific studies on the feasibility of inland waterways in Malaysia in term of technicality, environmental impact, social development and economic development should be initiated.